STUDENTS' SOCIAL ACTIVITIES AS A GUARANTEE OF THEIR PROFESSIONAL SUCCESS - Aues M. Kumykov; Azamat Kh. Lyuev; Gyulnara A. Zhabelova; Kseniya N. Zhuravel (Высшее образование в России)
The paper analyzes the features of educational process, realization of youth policy and collective self-organization of students at Kabardino-Balkarian State University. The experience of student's' self-government and co-government forms improvement is presented.